Tìm x, biết:
1.7⋮ (2x - 1)
2. 7 x∈Ư (2x -1)
3. -7⋮ ( x + 8)
Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.
Tìm x thuộc N
1) ( 2x + 3) thuộc B(x - 2 )
2) ( x + 1 ) thuộc Ư( 2x + 7)
3) ( 3x + 12) thuộc B( 3x + 7)
1: 7-x=8+(-7)
=>7-x=8-7=1
=>x=7-1=6
2: \(x-8=\left(-3\right)-8\)
=>x-8=-11
=>\(x=-11+8=-3\)
3: \(2-x=10-9+23\)
=>\(2-x=33-9=24\)
=>x=2-24=-22
4: \(-2-x=15\)
=>\(x=-2-15=-17\)
5: \(-7+x-8=-3-1+13\)
=>x-14=13-4=9
=>x=9+14=23
6: 100-x+7=-x+3
=>107-x=3-x
=>107=3(vô lý)
7: \(23+x=8-2x\)
=>\(x+2x=8-23\)
=>3x=-15
=>x=-15/3=-5
( x - 1 )( x + 2 ) - x - 2 = 0
<=> ( x - 1 )( x + 2 ) - ( x + 2 ) = 0
<=> ( x + 2 )( x - 2 ) = 0
<=> x = ±2
( 2x - 7 )3 = 8( 7 - 2x )2
<=> ( 2x - 7 )3 - 8( 2x - 7 )2 = 0
<=> ( 2x - 7 )2( 2x - 15 ) = 0
<=> x = 7/2 hoặc x = 15/2
a. \(\dfrac{8}{7}-\dfrac{1}{7}:\left(\dfrac{x}{3}-2\right)=-1\)
\(-\dfrac{1}{7}:\left(\dfrac{x}{3}-2\right)=\dfrac{15}{7}\)
\(\dfrac{x}{3}-2=\dfrac{-1}{15}\)
\(\dfrac{x}{3}=\dfrac{29}{15}\)
\(x=5,8\)
b. \(\dfrac{5}{8}+\dfrac{1}{4}\left(2x-1\right)=\dfrac{5}{4}\)
\(\dfrac{1}{4}\left(2x-1\right)=\dfrac{5}{8}\)
\(2x-1=\dfrac{5}{2}\)
\(2x=\dfrac{7}{2}\)
\(x=\dfrac{7}{4}\)
a) \(\left(x+1\right)^2=3\left(x+1\right)\)
\(\Leftrightarrow\left(x+1\right)^2-3\left(x+1\right)=0\)
\(\Leftrightarrow\left(x+1\right)\left(x-2\right)=0\)
\(\Leftrightarrow\orbr{\begin{cases}x+1=0\\x-2=0\end{cases}}\Rightarrow\orbr{\begin{cases}x=-1\\x=2\end{cases}}\)
b) \(\left(2x-7\right)^3=8\left(7-2x\right)^2\)
\(\Leftrightarrow\left(2x-7\right)^3-8\left(2x-7\right)^2=0\)
\(\Leftrightarrow\left(2x-7\right)^2\left(2x-15\right)=0\)
\(\Leftrightarrow\orbr{\begin{cases}\left(2x-7\right)^2=0\\2x-15=0\end{cases}}\Leftrightarrow\orbr{\begin{cases}2x=7\\2x=15\end{cases}}\Leftrightarrow\orbr{\begin{cases}x=\frac{7}{2}\\x=\frac{15}{2}\end{cases}}\)
a, \(\left(x+1\right)^2=3\left(x+1\right)\Leftrightarrow x^2+2x+1=3x+3\)
\(\Leftrightarrow x^2-x-2=0\Leftrightarrow\left(x-2\right)\left(x+1\right)=0\Leftrightarrow\orbr{\begin{cases}x=-2\\x=1\end{cases}}\)
b, \(\left(2x-7\right)^3=8\left(7-2x\right)^2\)
\(\Leftrightarrow8x^3-116x^2+518x-735=0\Leftrightarrow\orbr{\begin{cases}x=3,5\\x=7,5\end{cases}}\)
\(12\left(x-3\right)=5\left(x-1\right)+4\)
\(\Rightarrow12x-36=5x-5+4\)
\(\Rightarrow12x-5x=-5+4+36\)
\(\Rightarrow7x=35\)
\(\Rightarrow x=5\)
\(-6\left(x-7\right)+2\left(x+10\right)=x-18\)
\(-6x+42+2x+20=x-18\)
\(-6x+2x-x=-18-20-42\)
\(-5x=-80\)
\(x=16\)
\(7\left(2x-1\right)-12\left(x-5\right)=3\)
\(\Rightarrow14x-7-12x+60=3\)
\(\Rightarrow14x-12x=3-60+7\)
\(\Rightarrow2x=-50\)
\(\Rightarrow x=-25\)
\(\left|2x-1\right|=17\)
\(\Leftrightarrow\orbr{\begin{cases}2x-1=17\\2x-1=-17\end{cases}}\)
\(\Leftrightarrow\orbr{\begin{cases}x=9\\x=-8\end{cases}}\)
\(\left|8-3x\right|=14\)
\(\Leftrightarrow\orbr{\begin{cases}8-3x=14\\8-3x=-14\end{cases}}\)
\(\Leftrightarrow\orbr{\begin{cases}x=-2\\x=\frac{22}{3}\end{cases}}\)
1: =>\(2x-1\in\left\{1;-1;7;-7\right\}\)
=>\(x\in\left\{1;0;4;-3\right\}\)
3: =>\(x+8\in\left\{1;-1;7;-7\right\}\)
=>\(x\in\left\{-7;-9;-1;-15\right\}\)